Preventing Theft with Aggravated Circumstances: Role of Samapta Unit of Brebes Police Department - Solekhah Solekhah; Harris Pasya (The Indonesian Journal of International Clinical Legal Education, 2023)
The purpose of this study was to analyze the implementation motorcycle patrols to prevent aggravated theft. This study used a qualitative approach with a field research method. The data was collected through interviews, observation, document study, while the data validity used data triangulation. This study found that aggravated theft was a prominent case in Brebes. The role of motorcycle patrol in preventing theft was not yet optimal because there were deficiencies in each stage of patrol management based on Chief of Security Mantainance Agancy Regulation (Perkabaharkam) No. 1 of 2017 and management theory. All the stages were affected by a shortage of personnel and some stages that were conducted only for formality. Through the six main management factors, there are supporting and inhibiting elements in the realization of the role of patrol. Patrolling plays an important role in preventing aggravated thefts. This research found influencing factors and proposed strategies to optimize motorcycle patrols in preventing aggravated thefts in Brebes Police jurisdiction. With the increasing number of thefts, the role of motorcycle patrol by Police Patrol Unit is needed. This research highlighted the need for improved bureaucracy in Police Patrol Unit, equal distribution of personnel according to the required number of personnel (DSP), development trainings on patrols, revision of standard opreating procedures on motorcycle patrols and crime mapping on aggravated thefts.